A Preview On Vehicle Routing System - Nurcahyo, Gunadi W.; Alias, Rose Alinda; Shamsuddin, Siti Mariyam; Md. Sap, Mohd. Noor (Penerbit UTM Press, 2001)
Vehicle Routing Problem is one of the important issues that exist in transportation systems. Many researchers have been working in this area to discover new methodologies in selecting the best routes in order to find better techniques for different types of problems found in Vehicle Routing Problems. This paper presents the most common types of problems solved by past researchers. A discussion is given to study the characteristics of problems addressed by the researchers. Based on the characteristics of the problems, new issues that have not been covered by provided solutions are introduced for future improvement.